BUDGET POLICY FOR COMMUNITY EMPOWERMENT TOWARDS ADVANCED VILLAGES : A CASE STUDY OF HILIAURIFA VILLAGE, SOUTH NIAS - Kristianus Dakhi; Tonny P. Situmorang; Warjio (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze community empowerment budget policy as a strategic instrument in accelerating rural development, with a case study in Hiliaurifa Village, Maniamolo Subdistrict, South Nias Regency. The focus of the study is on the implementation of budget policy in supporting empowerment programs and its impact on rural progress. The approach used is descriptive qualitative with data collection techniques through in-depth interviews with the Village Head, BPD Chair, Hamlet Head, and community members, field observations, and analysis of the 2023–2024 APBDes documents. The results of the study show that the allocation of Village Funds has contributed significantly to empowerment programs and village development. Over the past two years, the Village Fund budget of Rp1,020,176,000.00 (2023) and Rp1,092,267,000.00 (2024) has been allocated to two main areas: village development and community empowerment. The utilization of these budgets has had a positive impact, particularly in enhancing community capacity and advancing village infrastructure. The study’s conclusions emphasize the importance of transparency and participation in the budget planning process. Recommendations include budget management training for village officials, guidance from the district government, and strengthening village deliberative forums as a collective decision-making mechanism supporting empowerment toward a progressive and self-reliant Hiliaurifa Village.